Postoperative pulmonary embolism in neurosurgical patients: increased mortality factors and prevention - Sergiy Minov; Anna Nikiforova; Viktor Yatsyk; Oleksandr Parkhomenko; Olena Mironenko; Oleksandr Zhurahivskiy; Igor Rostotskiy; Dmytro Kuzmenko (Ukrainian Neurosurgical Journal, 2016)
Objectives: Propose methods of prevention of thromboembolic complications in neurosurgical patients in the postoperative period, taking into account risk factors for death due to pulmonary embolism (PE).Materials and methods. We made a retrospective study of the clinical histories of 163 neurosurgical patients operated between 2010 and 2014. Patients were divided into two groups: the first consisted of patients who died in the postoperative period due to pulmonary embolism (n=63), second (control) - patients in the postoperative period and at discharge had no thromboembolic complications (n=100).Results. No gender differences are found, death due to thromboembolic complication occurs equally in men and women (relative risk — RR=1; 95% confidence interval — CI 0.68–1.48; p=0.99).The risk of death from pulmonary embolism at the patient aged 41-60 is higher in 2 times than the patient aged 18-40 (RR=2.00; 95% CI 0.94–4.26; p=0.07), in patients older than 60 years of age is higher in 2.5 times than the patients aged 18-40 (RR=2.50; 95% CI 1.14–5.47; p=0.02).Patients with thrombophlebitis of lower extremities due to pulmonary embolism die almost three times more than in its absence (RR=2.98; 95% CI 2.29–3.8; p=0.00); likely to die in the postoperative period due to pulmonary embolism in patients with hypertension in 2.61 higher than in patients with normal pressure (RR=2.61; 95% CI 1.64–4.15; p=0.00); atrial fibrillation and flutter increases the risk of death from pulmonary embolism in more than 2 times compared with patients who did not have such pathology (RR=2.11; 95% CI 1.48-2.99; p=0.00).High hematocrit levels and diabetes increase the risk of death from pulmonary embolism in 1.4 and 1.21 times (respectively). But P value of 0.09 and 0.56 is non-statistically significant results at an alpha level of 0.05. Also the lower limit of the CI (0.96 and 0.65) does not cross the line no effect (1.0). Therefore this factors that actually effect slightly, but finality of this conclusion needs further study.Obesity is not a risk factor for death from pulmonary embolism (RR=0.92; 95% CI 0.52–1.61; р=0.77).Conclusions. 1. Significant factors for increased risk of death from pulmonary embolism in patients with neurosurgical disorders are age over 40 years, thrombophlebitis of lower limbs, hypertension and arrhythmia or atrial fibrillation; diabetes and elevated hematocrit levels not significantly increase the risk of death from pulmonary embolism; gender and obesity did not increase the risk of death from pulmonary embolism.2. In order to prevent the death of neurosurgical patients due to pulmonary embolism depending on the risk groups we recommend: elastic graduated compression stockings in preoperative, intraoperative and postoperative phases; early and frequent ambulation; adequate hydration; intermittent pneumatic compression; use low molecular weight heparin (LMWH) and unfractionated heparin (UFH) later a few days after surgery at the stabilization of hemostasis and under the strict control of blood coagulation.